DUSP22 suppresses prostate cancer proliferation by targeting the EGFR‐AR axis. Issue 12 (5th November 2019) - Lin, Hsiu‐Ping; Ho, Hui‐Min; Chang, Cheng‐Wei; Yeh, Shauh‐Der; Su, Yu‐Wen; Tan, Tse‐Hua; Lin, Wen‐Jye
Abstract : Dual‐specificity phosphatases (DUSPs) regulate the activity of various downstream kinases through serine or threonine or tyrosine dephosphorylation. Loss of function and aberrant expression of DUSPs has been implicated in cancer progression and poor survival, yet the function of DUSP22 in prostate cancer (PCa) cells is not clear. Gene Expression Omnibus and cBioPortal microarray database analyses showed that DUSP22 expression was lower in PCa tissues than normal prostate tissues, and altered DUSP22 expression was associated with shorter progression‐free and disease‐free survival of patients with PCa. Exogenous DUSP22 expression in LNCaP, PC3, and C4‐2B PCa cells inhibited cellular proliferation and colony formation, supporting a growth inhibitory role for DUSP22 in PCa cells. DUSP22 expression significantly attenuated epidermal growth factor (EGF) receptor (EGFR) and its downstream ERK1/2 signaling by dephosphorylation. However, DUSP22 failed to suppress the growth of CWR22Rv1 and DU145 cells with elevated phosphorylated (p‐)ERK1/2 levels. A serine‐to‐alanine mutation at position 58, a potential ERK1/2‐targeted phosphorylation site in DUSP22, was sufficient to suppress growth of CWR22Rv1 cells with elevated p‐ERK1/2 levels, suggesting a mutually antagonistic relationship between DUSP22 and ERK1/2 dependent on phosphorylation status. We showed that DUSP22 can suppress prostate‐specific antigen gene expression through phosphatase‐dependent pathways, suggesting that DUSP22 is an important regulator of the androgen receptor (AR) in PCa cells. Mechanistically, DUSP22 can interact with AR as a regulatory partner and interfere with EGF‐induced AR phosphorylation at Tyr534, suggesting that DUSP22 serves as a crucial suppressor of both EGFR and AR‐dependent signaling in PCa cells via dephosphorylation. Our findings indicate that loss of function of DUSP22 in PCa cells leads to aberrant activation of both EGFR‐ERKs and AR signaling and ultimately progression of PCa, supporting the potential for novel therapeutic design of harnessing DUSP22 in the treatment of PCa.—Lin, H.‐P., Ho, H.‐M., Chang, C.‐W., Yeh, S.‐D., Su, Y.‐W., Tan, T.‐H., Lin, W.‐J. DUSP22 suppresses prostate cancer proliferation by targeting the EGFR‐AR axis. FASEB J. 33, 14653‐14667 (2019). www.fasebj.org